1992
DOI: 10.1002/anie.199202473
|View full text |Cite
|
Sign up to set email alerts
|

Benzene and Its Derivatives as Bridging Ligands in Transition‐Metal Complexes

Abstract: Transition-metal complexes in which two or more metal atoms are bridged by one or more arene ligands led a shadowy existence in comparison to the extensive class of mononuclear arene complexes. Arene bridges can occur in a variety of coordination modes and with almost all of the transition-metal elements of the periodic table. Nowhere else are found so many forms of distorted and bent arene rings. The binuclear compounds can be divided into two classes : adducts which show relatively weak metal-arene bonding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(36 citation statements)
references
References 125 publications
2
33
0
1
Order By: Relevance
“…Migration of the Cr(CO) 3 tripod moiety in 112 is much slower (kinetic energy barrier 32 kcal mol −1 ) and proceeds via an o ‐Y‐complex (a similar migration was utilised in the first organometallic latch, section 3.3). Haptotropic rotation, a close relative of trigonal rotors (sections 3.1–3.3), proceeds via six rotamers of unusual tris ‐cyclopentadienylcobalt complex 113 as shown by 1 H‐ 1 H EXSY; for R= i ‐Pr, the energy barrier is 13.6 kcal mol −1 . Independently, it was shown that five dynamic processes in a related Os carbonyl 114 remain detectable in the solid state …”
Section: Isomerisations and Rearrangementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Migration of the Cr(CO) 3 tripod moiety in 112 is much slower (kinetic energy barrier 32 kcal mol −1 ) and proceeds via an o ‐Y‐complex (a similar migration was utilised in the first organometallic latch, section 3.3). Haptotropic rotation, a close relative of trigonal rotors (sections 3.1–3.3), proceeds via six rotamers of unusual tris ‐cyclopentadienylcobalt complex 113 as shown by 1 H‐ 1 H EXSY; for R= i ‐Pr, the energy barrier is 13.6 kcal mol −1 . Independently, it was shown that five dynamic processes in a related Os carbonyl 114 remain detectable in the solid state …”
Section: Isomerisations and Rearrangementsmentioning
confidence: 98%
“…Haptotropic rotation, a close relative of trigonal rotors (sections 3.1-3.3), proceeds via six rotamerso fu nusual tris-cyclopentadienylcobalt complex 113 as shown by 1 H-1 HE XSY;f or R = i-Pr,t he energy barrieri s 13.6 kcal mol À1 . [183] Independently,i tw as shown that five dynamic processes in ar elated Os carbonyl 114 remaind etectable in the solid state. [184] Famously,t he s-p-s interconversion of h 1 -a nd h 3 -allylpalladium species,f or example, 115a$115b was shown to be involved in Pd-catalysed allylic substitution.…”
Section: Haptotropic Processesmentioning
confidence: 99%
“…The idea of using binuclear complexes for ligand activation has been recognized. , Understanding the properties of heterobimetallic catalysts would help explain how Ni and Fe cooperate in the various steps of acetyl-CoA synthesis. Both hetero- and homonuclear bimetallic complexes without metal−metal bonds are being studied. In these complexes, two or more metals are bridged by a common ligand. The joint action of two metal centers could enhance the activation of an organic substrate by several mechanisms.…”
Section: Is a Bimetallic System Better In A Chemical Biomimetic?mentioning
confidence: 99%
“…69 General information on the purification of additional starting materials, solvents and reagents, cyclic voltammetry, X-band cw-EPR spectroscopic and XRD data, computational details, and DFT-optimized structures is provided in the Supporting Information. 1 H and 13 C{ 1 H} NMR chemical shifts (δ) are referenced to residual 1 H and naturally abundant 13 C NMR resonances of the solvents (cf. the Supporting Information).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The group of electron acceptors comprises ligands that interconvert between a neutral and a radical-anionic form. Suitable candidates are ligands with energetically accessible π* orbitals, such as (heterocyclic) arenes, conjugated N 4 -macrocycles, azo-1,2-dicarbonyl compounds, (conjugated) N derivatives of (di)­carbonyls, , and small (inorganic) molecules such as CO 2 , O 2 , or NO . The second category includes electron-donor ligands that establish an isomorphic series of distinct valence states that include closed-shell and (bi)­radical forms.…”
Section: Introductionmentioning
confidence: 99%